Changes in soil organic and inorganic carbon with elevation in a dry alpine rangeland of the northern Qinghai–Tibet Plateau - Q. Liu; A. Zhang; X. Li; J. Yin; Y. Zhang; O. J. Sun; O. J. Sun; Y. Jiang (Biogeosciences)
The spatial patterns of soil carbon (C) in water constrained alpine ecosystems have rarely been investigated. It remains unclear how changes in biotic and abiotic factors with elevation would shape the distribution of soil C stocks when plant communities are co-limited by water and low temperature. To address this uncertainty, we systematically set up seven sampling points along an elevational gradient between 3000 and 4000 m above sea level and investigated the patterns of changes with elevation in the surface soil organic C (SOC) and soil inorganic C (SIC) in the northern part of the Qinghai–Tibet Plateau. Our results showed that the total soil C density (TCD) and the SOC density (SOCD) increased with rising elevation, but the SIC density (SICD) displayed a pattern of nonlinear change with a peak at the mid-slope of the elevational range. While SIC dominated the soil C pool, accounting for 64 %–90 % of TCD, the proportion of SOC increased from 10 % of the TCD at the lower range of the elevational gradient to 36 % at the upper range. The increases in SOCD with elevation were associated with changes from scrub dominated vegetation cover to herbaceous plant communities and decreasing MAT, suggesting a dual mechanism SOC accumulation at the higher elevation by increased level of plant derived C inputs and reduced SOC mineralization. In contrast, variations in SICD were mainly explainable by changes in soil C to N ratio and soil water content (SWC) and likely resulted from non-linear changes in factors related to inorganic C production and leaking losses. Findings from this study help fill the knowledge gap on the underlying controls of SOC and SIC distribution with changes in elevation in water and low temperature constrained alpine rangeland.